The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Drug Discovery Research in Pharmacognosy 2012
DOI: 10.5772/32093
|View full text |Cite
|
Sign up to set email alerts
|

Natural Alkamides: Pharmacology, Chemistry and Distribution

Abstract: Alkamides are a broad and expanding group of bioactive natural compounds found in at least 33 plant families. Despite the relatively simple molecular architecture of alkamides (fig. 1), these natural products show broad structural variability and an important range of biological activities, such as immunomodulatory, antimicrobial, antiviral, larvicidal, insecticidal, diuretic, pungent, analgesic, cannabimimetic and antioxidant activities. Additionally, alkamides are involved in the potentiation of antibiotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Alkamides have mainly been reported in Piperaceae, Asteraceae, Rutaceae and Aristolochiaceae families (Rios, 2012). However, polyacetylenic alkamides have only been found in Asteraceae where they frequently occur in Anthemideae and Heliantheae tribes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkamides have mainly been reported in Piperaceae, Asteraceae, Rutaceae and Aristolochiaceae families (Rios, 2012). However, polyacetylenic alkamides have only been found in Asteraceae where they frequently occur in Anthemideae and Heliantheae tribes.…”
Section: Discussionmentioning
confidence: 99%
“…Most polyacetylenic cyclic amides found in this tribe consist of pyrrolidides and piperidides whereas polyacetylenic piperidides are rare (Bohlman, 1988;Bohlmann et al, 1973;Christensen, 1992;Greger, 1984Greger, , 1988. In this study, the novel antiacne compound identified belongs to the piperidide family, which are known to be antimicrobial, antiviral, larvicidal, insecticidal, diuretic, pungent, analgesic, cannabimimetic and antioxidant (Rios, 2012). Some of the plant sources that are known to have anti-acne effect are Aloe vera (Grace et al, 2008), Azadirachta indica, Curcuma longa, Hemidesmus incidus, Gossypium barbadense (Kanlayavattanakul and Lourith 2011), essential oils of Eucalyptus radiate and Melaleuca alternifolia (Stevensen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Alkamides are the major bioactive secondary metabolites in Echinacea and Lepidium spp. (Peruvian ginseng), , and these compounds are also responsible for both the pungent or spicy flavors and medicinal properties of chili ( Capsicum spp. ), Szechuan and Japanese pepper ( Zanthoxylum spp.…”
Section: Introductionmentioning
confidence: 99%
“…), Szechuan and Japanese pepper ( Zanthoxylum spp. ), and black pepper ( Piper nigrum ). The most abundant alkamides in P. nigrum peppercorns are piperine and piperyline (Figure B), although multiple others have been reported. Peppercorns are the fruits of the P. nigrum plant and are classified as “black”, “white”, “green”, or “red”, depending on when they are harvested and how they are processed.…”
Section: Introductionmentioning
confidence: 99%
“…The Asteraceae family is among the largest in the Mexican flora, and its ethnobotanical and ethnopharmacological reports have revealed therapeutic use due to its bioactive secondary metabolite diversity [2,3]. Among this plant family, some genera such as Acmella (formerly listed as Spilanthes) [4][5][6] stand out for producing several secondary metabolites, e.g., aliphatic alkamides in roots and flowers, which have analgesic effects on the teeth and throat [7][8][9], while polyphenols have anti-inflammatory, antiseptic, and antioxidant properties [10,11].…”
Section: Introductionmentioning
confidence: 99%